The sphingosine‐1‐phosphate signaling pathway (sphingosine‐1‐phosphate and its receptor, sphingosine kinase) and epilepsy - Lin Wang; Qingxia Kong; Xinyi Leng; Howan Leung; Yang Li (Epilepsia Open)
Abstract Epilepsy is one of the common chronic neurological diseases, affecting more than 70 million people worldwide. The brains of people with epilepsy exhibit a pathological and persistent propensity for recurrent seizures. Epilepsy often coexists with cardiovascular disease, cognitive dysfunction, depression, etc., which seriously affects the patient's quality of life. Although our understanding of epilepsy has advanced, the pathophysiological mechanisms leading to epileptogenesis, drug resistance, and associated comorbidities remain largely unknown. The use of newer antiepileptic drugs has increased, but this has not improved overall outcomes. We need to deeply study the pathogenesis of epilepsy and find drugs that can not only prevent the epileptogenesis and interfere with the process of epileptogenesis but also treat epilepsy comorbidities. Sphingosine‐1‐phosphate (S1P) is an important lipid molecule. It not only forms the basis of cell membranes but is also an important bioactive mediator. It can not only act as a second messenger in cells to activate downstream signaling pathways but can also exert biological effects by being secreted outside cells and binding to S1P receptors on the cell membrane. Fingolimod (FTY720) is the first S1P receptor modulator developed and approved for the treatment of multiple sclerosis. More and more studies have proven that the S1P signaling pathway is closely related to epilepsy, drug‐resistant epilepsy, epilepsy comorbidities, or other epilepsy‐causing diseases. However, there is much controversy over the role of certain natural molecules in the pathway and receptor modulators (such as FTY720) in epilepsy. Here, we summarize and analyze the role of the S1P signaling pathway in epilepsy, provide a basis for finding potential therapeutic targets and/or epileptogenic biomarkers, analyze the reasons for these controversies, and put forward our opinions. Plain Language Summary This article combines the latest research literature at home and abroad to review the sphingosine 1‐phosphate signaling pathway and epileptogenesis, drug‐resistant epilepsy, epilepsy comorbidities, other diseases that can cause epilepsy, as well as the sphingosine‐1‐phosphate signaling pathway regulators and epilepsy, with the expectation of providing a certain theoretical basis for finding potential epilepsy treatment targets and/or epileptogenic biomarkers in the sphingosine‐1‐phosphate signaling pathway.